1984
DOI: 10.1002/bem.2250050408
|View full text |Cite
|
Sign up to set email alerts
|

Formulas for preparing phantom muscle tissue at various radiofrequencies

Abstract: The dielectric properties of various test samples of phantom tissue were measured using an automated and temperature-controlled slotted line. The ingredients for phantom materials were determined for simulating high-water content tissue at 13.56, 27.12, 40.68, 70, 100, 200, 300, 433, 750, 915, and 2,450 MHz. The ingredients consisted of water, TX-150 (a gelling agent), sodium chloride, and polyethylene powder (200-2,450 MHz) or aluminum powder (13.56-100 MHz). The dielectric constant and conductivity of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
96
0
2

Year Published

1996
1996
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 239 publications
(98 citation statements)
references
References 12 publications
0
96
0
2
Order By: Relevance
“…Therefore, to fill this gap we present a radio propagation study for 2360-2500 MHz, which covers the two frequency bands discussed above with potential use for implant communications. We performed channel measurements in a liquid phantom, i.e., a chemical solution specially formulated to reproduce the dielectric properties of human muscle tissues [29]. We considered three different channel scenarios: in-body to in-body (IB2IB), in-body to onbody (IB2OB), and in-body to off-body (IB2OFF).…”
mentioning
confidence: 99%
“…Therefore, to fill this gap we present a radio propagation study for 2360-2500 MHz, which covers the two frequency bands discussed above with potential use for implant communications. We performed channel measurements in a liquid phantom, i.e., a chemical solution specially formulated to reproduce the dielectric properties of human muscle tissues [29]. We considered three different channel scenarios: in-body to in-body (IB2IB), in-body to onbody (IB2OB), and in-body to off-body (IB2OFF).…”
mentioning
confidence: 99%
“…After returning to China, Mr. Yang introduced dosimetry concepts to the Chinese National RF exposure standard GB8702-1988. Professor Chen Gang-Wu was in our lab for 1 year and participated in the development of phantom materials for simulating muscle tissue at 13.56-2450 MHz [Chou et al, 1984a]. These formulas for tissue simulating materials were later used in my hyperthermia studies when my work turned to medical applications.…”
Section: Dosimetrymentioning
confidence: 99%
“…Conductivities of Carbon-Black-Silicone Materials 11 4.6 Glycine-Based Phantom Material 14 5 Discussion 18 6 References 22 7 2.…”
Section: Contentsmentioning
confidence: 99%
“…Kato found that the semisolid material could be sculptured to produce a body shape, but degraded in time. Chou et al [6] used a mixture of water, salts, and a gelling agent to form a semi-solid material.…”
Section: Overview Of the Problemmentioning
confidence: 99%
See 1 more Smart Citation